Surface discrete breathers in Pt3Al intermetallic alloy - Zakharov, P. V. (2020)
It is known that defect-free crystals can support spatially localized, large amplitude vibrational modes with frequencies outside the linear phonon spectrum. Such excitations are called discrete breathers (DB) or intrinsic localized modes. So far, for 3D crystals DB were considered only in the bulk. In the present molecular dynamics study, for the first time, we demonstrate that DB can be excited at the low Miller indices surfaces of the Pt3Al intermetallic alloy. It is shown that properties of the DB depend essentially on the surface orientation and termination, as well as on DB polarization. The study of DB at crystal surfaces is important because they can localize energy of order of 1 eV, which can reduce the potential barrier for local structure transformation or a chemical reaction.